2007
DOI: 10.3803/jkes.2007.22.1.68
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Familial Multiple Endocrine Neoplasia Type 1 with MEN1 Gene Mutation

Abstract: -68 - Herein is reported the case of a 26-year-old woman who had complained of personality and behavior changes, coupled with repetitive loss of consciousness. Her random plasma glucose and insulin were 68 mg/dL and 67.3 μIU/mL, respectively. Two pancreatic masses were noted on abdominal computed tomography, with hypercalcemia noted from a routine chemistry test. Her diagnosis was that of MEN1; therefore, her first-degree relatives were also screened. DNA analysis was also performed, from which a MEN1 gene mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We first reviewed the medical records of 14 unrelated MEN1 patients who had germline mutations of the MENIN gene confirmed in Severance Hospital (Seoul, Korea). We evaluated the extended data from a total of 28 unrelated patients including 14 cases in the present study and 14 cases previously reported with genetic confirmation in Korea by searching on PubMed and KoreaMed [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The clinical characteristics of six family members were collected for MENIN germline mutation carriers to analyze any relationship between genotypes and phenotypes.…”
Section: Methodsmentioning
confidence: 99%
“…We first reviewed the medical records of 14 unrelated MEN1 patients who had germline mutations of the MENIN gene confirmed in Severance Hospital (Seoul, Korea). We evaluated the extended data from a total of 28 unrelated patients including 14 cases in the present study and 14 cases previously reported with genetic confirmation in Korea by searching on PubMed and KoreaMed [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The clinical characteristics of six family members were collected for MENIN germline mutation carriers to analyze any relationship between genotypes and phenotypes.…”
Section: Methodsmentioning
confidence: 99%